Can AI Make Ethical Medical Decisions? Navigating the Moral Landscape of Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Can AI Make Ethical Medical Decisions? Navigating the Moral Landscape of Digital Health The integration of Artificial Intelligence (AI) into clinical pr...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care